2008
DOI: 10.4171/ifb/187
|View full text |Cite
|
Sign up to set email alerts
|

On the energy of a flow arising in shape optimization

Abstract: In [8] we have defined a viscosity solution for the gradient flow of the exterior Bernoulli free boundary problem. We prove here that the associated energy is non-increasing along the flow. For this we build a discrete gradient flow in the flavour of Almgren, Taylor and Wang [2].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…We remark that 13) where the constant C is a bound on the perimeter of {u(·, t) = 0}, uniform for u ∈ E and t ∈ [0, t 0 ].…”
Section: Lemma 75 (Estimate On Characteristic Functions) There Exismentioning
confidence: 99%
“…We remark that 13) where the constant C is a bound on the perimeter of {u(·, t) = 0}, uniform for u ∈ E and t ∈ [0, t 0 ].…”
Section: Lemma 75 (Estimate On Characteristic Functions) There Exismentioning
confidence: 99%
“…The flow of the shape gradient then formally leads to an Hamilton-Jacobi equation for the evolution of the domain coupled with the state function. Recently, Cardaliaguet and Ley have performed in [7,8] a first step in the theoretical justification of this approach on a specific example. However, the level set grid has no particular reason to be useful for the computation of the state function.…”
Section: Introductionmentioning
confidence: 99%
“…Such appears in the study of viscosity solutions when there are possibilities of nonuniqueness/fattening of the zero set (see for example [2]). …”
Section: The Continuum Limit and Existence Of Weak Solutionsmentioning
confidence: 99%
“…In [3] it was shown that a particular selection of the discrete scheme in [1] converges to viscosity solution of the mean curvature flow in the sense of [6]. Also see [2] where one studies a free boundary problem similar to (P), but satisfies the comparison principle. (In [2] the goal was to obtain an energy bound for the viscosity solution of the corresponding problem.…”
mentioning
confidence: 99%
See 1 more Smart Citation